JAM’ AL TAKSĪR DALAM AL QUR’AN JUZ 1-10 (ANALISIS MORFOSINTAKSIS). - Luthfirif'atul Maghfiroh; Zaim Elmubarok; Multazam Multazam (Lisanul Arab: Journal of Arabic Learning and Teaching, 2022)
Jama' taksīr included the classification of Arabic nouns in number. The jama' taksīr classification in morphogenetic studies discuss processes of formation, cases, changes in grammatical bookmarks, and syntax functions. The research aims to describe the form of jama' taksīr in the qur 'an in juz 1-10 and explain the jama' taksīr analysis in the juz 1-10 of qur'an reviewing morphogenetic studies. It is a descriptive study with a qualitative approach. The study used content analysis as a research study. The data in this study is the written data of fragments of qur'an containing the jama' taksīr. Data collection techniques are conducted with predetermined elemental computing techniques, their tools being the mental effects of researchers. Research instruments are the researchers themselves aided by data cards. The study uses inductive data analysis techniques. The research found 94 data of jama' taksīr, consisting of 33 data of qillah (minor plural), 43 data of 'kasrah (major plural). According to syntax function, there are three cases in the JAM’ AL TAKSĪR analysed data, comprise 23 counts, 33 archivists, and 38 genetical-case data